Evaluation of cast creep occurring during simulated clubfoot correction. (August 2013) - Cohen, Tamara L; Altiok, Haluk; Wang, Mei; McGrady, Linda M; Krzak, Joseph; Graf, Adam; Tarima, Sergey; Smith, Peter A; Harris, Gerald F
The Ponseti method is a widely accepted and highly successful conservative treatment of pediatric clubfoot involving weekly manipulations and cast applications. Qualitative assessments have indicated the potential success of the technique with cast materials other than standard plaster of Paris. However, guidelines for clubfoot correction based on the mechanical response of these materials have yet to be investigated. The current study sought to characterize and compare the ability of three standard cast materials to maintain the Ponseti-corrected foot position by evaluating cast creep response. A dynamic cast testing device, built to model clubfoot correction, was wrapped in plaster of Paris, semi-rigid fiberglass, and rigid fiberglass. Three-dimensional motion responses to two joint stiffnesses were recorded. Rotational creep displacement and linearity of the limb-cast composite were analyzed. Minimal change in position over time was found for all materials. Among cast materials, the rotational creep displacement was significantly different ( p < 0.0001). The most creep displacement occurred in the plaster of Paris (2.0°), then the semi-rigid fiberglass (1.0°), and then the rigid fiberglass (0.4°). Torque magnitude did not affect creep displacement response. Analysis of normalized rotation showed quasi-linear viscoelastic behavior. This study provided a mechanical evaluation of cast material performance as used for clubfoot correction. Creep displacement dependence on cast material and insensitivity to torque were discovered. This information may provide a quantitative and mechanical basis for future innovations for clubfoot care.